Upgrading the post-harvest process of ISRA breeding programs - Oumar Diack; Diatta, Cyril; Ibrahima Sarr; Inoussa Dabo; Nebie, Baloua (International Maize and Wheat Improvement Center, 2024)
ISRA's post-harvest breeding programs processing capacity has been improved and modernized through its collaboration with CIMMYT.